Future breeding and foraging sites of a southern edge population of the locally endangered Black Guillemot Cepphus grylle. Issue 3 (3rd July 2017) - Buchadas, Ana R.C.; Hof, Anouschka R.
ABSTRACT: Capsule: One of the southernmost populations of the Black Guillemot Cepphus grylle is currently endangered, and the risk may be exacerbated by climate change. Aims: We evaluated the future vulnerability of the Black Guillemot by predicting the impact of climate change on the geographic distribution of its breeding and foraging range in the Baltic Sea. Methods: We used MaxEnt, a species distribution modelling technique, to predict the current and future breeding grounds and foraging sites. Results: We found that although the foraging range is expected to increase in the southern Baltic Sea in future, these areas will no longer be suitable as breeding grounds due to a changing climate, creating a spatial mismatch. Conclusion: Our predictions indicate where threats to the species may be most severe and can be used to guide conservation planning. We advocate conservation measures which integrate potential future threats and focus on breeding sites across the current and future potential geographic range of the Black Guillemot.